2021
DOI: 10.3390/genes12030386
|View full text |Cite
|
Sign up to set email alerts
|

Olive (Olea europaea L.) Genetic Transformation: Current Status and Future Prospects

Abstract: Olive (Olea europaea L.) is the most characteristic and important oil crop of the Mediterranean region. Traditional olive cultivation is based on few tens cultivars of ancient origin. To improve this crop, novel selections with higher tolerance to biotic and abiotic stress, adaptable to high-density planting systems and resilient to climate change are needed; however, breeding programs are hindered by the long juvenile period of this species and few improved genotypes have been released so far. Genetic transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…The information generated using SNP-based approaches may allow us to discover genes/alleles useful for enhancing target traits, while new advanced biotechnologies, such as transformation-based editing methods, allow us to transfer them to elite cultivars. Improvements in transformation and regeneration protocols in a recalcitrant species such as the olive are continually reported, and important traits such as resistance to fungi, flowering, or lipid composition, have already been successfully manipulated [96][97][98].…”
Section: Perspectivesmentioning
confidence: 99%
“…The information generated using SNP-based approaches may allow us to discover genes/alleles useful for enhancing target traits, while new advanced biotechnologies, such as transformation-based editing methods, allow us to transfer them to elite cultivars. Improvements in transformation and regeneration protocols in a recalcitrant species such as the olive are continually reported, and important traits such as resistance to fungi, flowering, or lipid composition, have already been successfully manipulated [96][97][98].…”
Section: Perspectivesmentioning
confidence: 99%
“…Types Were Involved in the Embryogenic Calli Protocol of Catalpa bungei Embryogenic calli induction and regeneration is a process that limits the establishment of efficient genetic transformation systems (Palomo-Rios et al, 2021). Genotype is considered the determinant factor in the success of this process in plant species because protocols suitable for one embryogenesis line or clones may not necessarily apply to others (Petri and Burgos, 2005).…”
Section: Multiple Genotypes and Multiple Explantmentioning
confidence: 99%
“…Genotype is considered the determinant factor in the success of this process in plant species because protocols suitable for one embryogenesis line or clones may not necessarily apply to others (Petri and Burgos, 2005). Only one or two EC genotypes were developed in previous genetic transformation protocols of woody plants, such as Paulownia elongata (Bajaj et al, 2021), olive (Olea europaea L.) (Narvaez et al, 2019;Palomo-Rios et al, 2021), Cork oak (Quercus suber L.) (Alvarez et al, 2004;Cano et al, 2021), European chestnut (Corredoira et al, 2016), and tea (Camellia sinensis) (Mondal et al, 2001). In this study, we obtained five EC genotypes, including two types of EC initiated from mature seed explants and three types from stem segment explants, which indicated that our constructed EC protocol was independent of genotype; therefore, it might be able to be extended to elite cultivars.…”
Section: Multiple Genotypes and Multiple Explantmentioning
confidence: 99%
“…Biotechnological approaches to improve this crop are also difficult to apply due to the recalcitrance of olive tissues to regenerate in vitro . Along this line, few transgenic olive plants have been generated ( Palomo-Ríos et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%